Condições de um latossolo vermelho amarelo eutrófico submetido à diversos sistemas de manejo na cultura do algodão (Gossypium hirsutum L.) - Ramos, Denis Tomás (2017)
The aim of this work was to characterize the conditions of a Eutrophic Yellow Red Latosol under different management systems and their interaction with the cotton crop development in the Cerrado region of Mato Grosso. Four management systems were evaluated: SCSRA - Conventional system with no cotton rotation, with soil turning and sowing over millet succession; SCCR - Minimum cultivation system with soybean / cotton rotation; SPDM - Cottonseed system in subsoil of Crotalaria Ochroleuca and SPDA – Cottonseed system in subsoil of Maize + Brachiaria Ruziziensis. Factor analysis was used to identify key indicators, in order to distinguish management systems from their functional clusters, between different layers. Notillage systems presented better soil quality indexes compared to conventional management systems (0.34 and 0.28 respectively). Both systems presented good productive performance, but with functional capacity representing 66% below their functional potential for conservationist systems and 72% for conventional ones. The nutrient retention capacity and nutrient availability showed a higher potential of the soil quality index weighting between 0 to 20 cm for the surface layers in conservationist systems, while the amount of available nutrients provided better weighting in conventional systems. However, the capacity of conservation and conduction of water presented greater potential of weighting of the index in the subsurface layers 20-40 cm, representing 46, 4% for conservationist systems and 52,8% for conventional ones. The use of corn + Brachiaria Ruziziensis rotation and cotton in no - tillage and the succession of millet and cotton in a system with soil rotation improved the quality index. These systems strongly favored the organic matter content and the microbial activity in the profile, with effective contribution to the formation of larger aggregates (4 to 2 and 2 to 1 mm) and, subsequently, obtaining better averages compared to the dry mass of the aerial part. The SPDA system showed a lower ratio of volume roots to depth (20 to 40 cm). On the other hand, the systems with succession Crotalaria / cotton under no-tillage and soybean / cotton under conventional system did not provide significant distinction in the pore distribution, in the mass of stable aggregates contained in the class of macro aggregates (4 -1 mm). There was a strong decrease of organic matter in the profile and microbial activity and an increase in the formation of micro aggregates (1- 0.25 mm), besides promoting reduction of root volume and dry mass (g.cm3). The low saturation of potassium, phosphorus and boron caused a restriction in the index in the functional chemical quality of the soil, causing limited responsiveness and low performance of the cotton crop in the Cerrado, not mattering the management system implemented.